Correction: Selective precipitation of alkyl dihalides using a newly synthesized water-soluble bisphosphorylpillar[5]arene. Issue 78 (13th September 2016) - Cheng, Wenjin; Tang, Hao; Wang, Rongrong; Wang, Lingyun; Meier, Herbert; Cao, Derong
Abstract : Correction for 'Selective precipitation of alkyl dihalides using a newly synthesized water-soluble bisphosphorylpillar[5]arene' by Wenjin Cheng et al., Chem. Commun., 2016, 52, 8075–8078.